(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
The National Széchényi Library (Országos Széchényi Könyvtár) in Budapest holds a small kajkavian catechism with a spelling book registered under number 301 879. It has 8 pages and the 15 cm spine. There is no data on the time or place of its printing. There have been no accounts or studies of this publication, and as it is completely unknown to the Croatian scientific community, it is reprinted in this issue of Libellarium. (Zoran Velagić)